The Art of Software Modeling - Lieberman, Benjamin (CRC Press, 2009)
Modeling complex systems is a difficult challenge and all too often one in which modelers are left to their own devices. Using a multidisciplinary approach, The Art of Software Modeling covers theory, practice, and presentation in detail. It focuses on the importance of model creation and demonstrates how to create meaningful models.